Haptic-based interaction and game design and development in co-spaces - Oh, Zhan Yang. (2011)
Haptic technology was first used in aircraft industry which uses servomechanism systems to operate control systems. It tends to be “one-way” in that forces applied aerodynamically to control surfaces are not perceived at the controls, with the missing normal forces simulated with springs and weight. Furthermore, force feedback has been implemented experimentally in some excavators. It allows the operator to “feel” and work around unseen obstacles, enabling significant increases in productivity.